Method for in-situ construction of solid electrolyte interfacial film on lithium metal surface by using organic acid anhydride
By constructing a LiF-rich SEI layer in situ on the lithium metal surface, the problem of low SEI structure strength in lithium metal batteries is solved, and the cycle stability and safety performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202510001602.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
The solid electrolyte interface mask (SEI) of existing lithium metal batteries has low structural strength, resulting in the generation of lithium dendrites and dead lithium, affecting the cycling performance and safety of the battery.
By constructing artificial SEI in situ on the surface of lithium metal, using organic anhydride to react directly with lithium metal, a LiF-rich SEI layer is generated to control the thickness and structure of SEI.
Effectively inhibit the side reaction between lithium metal and electrolyte, reduce the generation of lithium dendrites, improve the cycle stability and safety performance of the battery, and extend the service life of the battery.
Smart Images

Figure CN119812225A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium batteries, in particular to a method for in-situ constructing a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride. Background Art
[0002] With the growing demand for rechargeable energy in portable electronics, electric vehicles, and large-scale grid energy storage devices, lithium batteries with higher energy density are urgently needed. The energy density of graphite-based and silicon-based lithium-ion batteries is approaching the upper limit of 350Wh / kg. Metal lithium anodes are regarded as one of the most ideal candidate materials for next-generation battery technology due to their high theoretical specific capacity (3857mAh / g) and low reduction potential (-3.04V compared to standard hydrogen electrodes). However, highly reactive lithium metal reacts easily with organic electrolytes to form a fragile and uneven solid electrolyte interface (SEI), which is broken and powdered during battery cycling due to the inability to withstand the huge volume expansion of the lithium metal anode, and exposes fresh lithium to the electrolyte, causing continuous reconstruction of the SEI and uneven lithium deposition, forming dangerous lithium dendrites and more inactive lithium deposition, which leads to poor cycling performance and low coulombic efficiency of lithium metal batteries. Lithium dendrites may even pierce the diaphragm and cause internal short circuits, thus causing safety hazards. These problems have greatly limited the practical application of lithium metal batteries. Therefore, a robust SEI with excellent structural stability is crucial for high-performance Li metal batteries.
[0003] In order to solve these problems, many targeted studies have been carried out, including polymer protective layers, alloy materials, electrolyte additives, artificial solid electrolyte interface films, modified diaphragms and three-dimensional current collectors. These improvement strategies are all aimed at obtaining a stable SEI for regulating the uniform deposition of lithium, so as to obtain a lithium metal battery with good performance. For example, patent document CN114583172A uses tetrafluoroethylene-hexafluoropropylene (PVDF-HFP) to be coated on the surface of lithium metal to inhibit the growth of lithium dendrites, but the ionic conductivity of the polymer material is low, especially at room temperature, which is not conducive to the realization of high-performance batteries. Patent document CN117638006A uses fluorinated high entropy alloy SEI to protect the lithium metal negative electrode, but the alloy material often causes mechanical instability due to excessive volume change during the cycle. In addition, the lithium-magnesium alloy will have a strong side reaction with the electrolyte to generate a passivation film, which limits the kinetic performance of the lithium battery and leads to its poor rate performance. Patent document CN115323412A prepares a difluoroethylene carbonate electrolyte additive, which is intended to regulate the native SEI to improve battery performance, but carbonate additives will react with lithium metal to generate lithium carbonate with poor conductivity and poor electrolyte wettability, which will lead to uneven interface contact, thereby inducing the growth of lithium dendrites. Patent document CN114976490A designs a stacked titanium dioxide modified diaphragm to regulate lithium ion deposition to inhibit the growth of lithium dendrites, but this cannot accurately control the composition and structure of SEI, and the side reaction between lithium metal and electrolyte will still affect the performance of the battery. Patent document CN104716330A designs a three-dimensional porous current collector to inhibit the growth of lithium dendrites. This current collector is prepared by chemical dealloying, electrochemical dealloying, electrochemical deposition or high-temperature metal sintering, and the process is relatively complicated. Not only that, the current collector structure obtained by these methods has poor strength and cannot adapt well to the long cycle charge and discharge of the battery.
[0004] From the perspective of these solutions, it is a feasible and convenient method to obtain artificial SEI by pretreating lithium metal. Because SEI with a stable structure can effectively inhibit the side reaction between lithium metal and organic electrolyte and inhibit the growth of lithium dendrites, and only the pretreatment conditions need to be changed to accurately construct the main components of SEI, which is easy to operate and simple in process. As we all know, LiF is a relatively important component in SEI. The presence of LiF helps to form a stable and ion-conductive passivation film on the electrode surface, improve the reversibility of the electrode reaction, and reduce the concentration polarization of the battery. LiF can also enhance the rate performance of the battery, increase the number of lithium ion migration, and increase the number of Li+ that can migrate in the electrolyte. The LiF-rich SEI layer has high mechanical strength and a compact and dense structure, which prevents lithium metal from breaking and pulverizing, inhibits the formation of lithium dendrites, and exhibits high Li+ conductivity. By directly reacting fluorine-containing organic anhydride solvents with lithium metal, an artificial SEI containing LiF is constructed in situ on the surface, inhibiting the adverse reactions between lithium metal and electrolyte, thereby promoting the stable cycle of lithium metal batteries and providing a new solution for the practical application of lithium metal batteries.
[0005] The prior art has the following defects:
[0006] 1) The original SEI structure has low strength and many side reaction products, which cannot effectively inhibit lithium dendrites and dead lithium;
[0007] 2) Compared with the SEI film prepared by the non-in-situ physical coating method, the in-situ construction will obtain a thin LiF-rich SEI film, which will not significantly increase the electrode mass and is conducive to improving the energy density of the battery;
[0008] 3) Ex situ methods cannot achieve precise control over the composition and structure of the SEI film. Summary of the invention
[0009] 1. Technical issues to be solved
[0010] In view of the deficiencies in the prior art, the present invention provides a method for constructing an artificial SEI in situ for a lithium metal battery. This method pre-treats the lithium metal sheet in situ, allowing the organic anhydride compound and the lithium metal to directly contact and react chemically, thereby pre-generating an artificial SEI in situ on the surface of the lithium metal. The lithium metal is pre-cleaned with an organic solvent to remove the surface passivation film as much as possible. The reaction time is controlled to control the degree of reaction between the lithium metal and the organic anhydride, thereby controlling the thickness of the artificial SEI. Because this method has already generated SEI on the surface of the lithium metal, it can effectively reduce the problem of electrolyte consumption caused by the generation of SEI in subsequent charge and discharge cycles, thereby extending the service life of the battery. In addition, this method can generate an SEI with controllable thickness on the surface of the lithium metal, and the operation is simple and the controllability is strong.
[0011] (II) Technical solution
[0012] To achieve the above objectives, the present invention is implemented by the following technical scheme: a method for in-situ construction of a solid electrolyte interface film on the surface of lithium metal using an organic acid anhydride, specifically comprising the following steps:
[0013] S1. Cleaning the surface of lithium metal: Select a lithium metal disc with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with an organic solvent, and remove impurities on the surface of the lithium metal as much as possible. After cleaning, lay the lithium disc flat, and modify the surface of the lithium metal after the organic solvent evaporates;
[0014] S2, Lithium metal surface modification: pour the organic acid anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step S1 horizontally into the culture dish, control the reaction time to 0.5-30min, and after the reaction is completed, wash the lithium metal surface with an organic solvent to remove the unreacted organic acid anhydride solution;
[0015] S3. Assembling lithium metal batteries or Li-Li symmetric batteries.
[0016] Preferably, when lithium metal battery assembly is used in step S3, the specific steps are as follows:
[0017] T1, using the organic anhydride modified lithium metal disc obtained in step S2 as the negative electrode of the battery, using 25 μm thick Celgard 2500 as the separator, using the positive electrode as an aluminum electrode with lithium iron phosphate as the active material, and using an organic solution of ethylene carbonate EC and diethyl carbonate DEC mixed with 1M lithium hexafluorophosphate as the electrolyte;
[0018] T2. Finally, use the CR-2032 battery shell to assemble the button battery.
[0019] Preferably, in step T1, the volume ratio of EC to DEC is 1:1, and the amount of electrolyte used in each battery is controlled at 80 μL.
[0020] Preferably, in step S3, when Li-Li symmetrical battery assembly is adopted, the specific steps are as follows:
[0021] E1. Select two lithium metal discs modified with the same organic anhydride in step S2 as the two electrodes of the symmetrical battery, use 25 μm thick Celgard 2500 as the separator, and use an organic solution of ethylene carbonate EC and diethyl carbonate DEC mixed with 1M lithium hexafluorophosphate LiPF6 as the electrolyte;
[0022] E2. Finally, use the CR-2032 battery shell to assemble the button battery.
[0023] Preferably, in step E1, the volume ratio of EC to DEC is 1:1, and the amount of electrolyte used in each battery is controlled at 80 μL.
[0024] Preferably, steps S1-S3 are all completed in a glove box, the overall atmosphere of the glove box is argon, and the oxygen content and water content are both below 0.01 ppm.
[0025] Preferably, the organic solvent in step S1 is one of tetrahydrofuran, diethyl ether, methyl tert-butyl ether or ethylene glycol dimethyl ether.
[0026] Preferably, the organic acid anhydride in step S2 is one of trifluoromethanesulfonic anhydride, difluoroacetic anhydride, trifluoroacetic anhydride, and heptafluorobutyric anhydride, and the amount poured in is sufficient to immerse the lithium metal.
[0027] (III) Beneficial effects
[0028] The present invention provides a method for in-situ construction of a solid electrolyte interface membrane on the surface of lithium metal using organic acid anhydride. Compared with the prior art, the method has the following beneficial effects: the method for in-situ construction of a solid electrolyte interface membrane on the surface of lithium metal using organic acid anhydride directly soaks lithium metal with organic acid anhydride to in-situ construct an artificial SEI with adjustable thickness on the surface of lithium metal, which can not only solve the problem of excessive consumption of electrolyte and lithium source, thereby slowing down the battery capacity attenuation and improving the long cycle performance of lithium metal batteries, but also the artificial SEI with high mechanical strength can inhibit the growth of lithium dendrites and improve the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the principle diagram of the present invention;
[0030] Figure 2 Schematic diagram of the surface morphology of lithium metal without any treatment in Comparative Example 1 of the present invention;
[0031] Figure 3 This is a schematic diagram of the surface morphology of lithium metal modified by trifluoromethanesulfonic anhydride in Example 1 of the present invention;
[0032] Figure 4 This is a schematic diagram of the surface morphology of lithium metal modified by trifluoroacetic anhydride in Example 2 of the present invention;
[0033] Figure 5 This is a schematic diagram of the surface morphology of lithium metal modified by difluoroacetic anhydride in Example 3 of the present invention;
[0034] Figure 6 This is a schematic diagram of the surface morphology of lithium metal modified by perfluorobutyric anhydride in Example 4 of the present invention;
[0035] Figure 70.5 mA cm in Example 1 and Comparative Example 1 -2 and 1mAh cm -2 Schematic diagram of symmetric battery performance;
[0036] Figure 8 1 mA cm of Example 1 and Comparative Example 1 -2 and 1mAh cm -2 Symmetrical battery performance graph;
[0037] Fig. 9 Schematic diagram of charge and discharge curves of Example 1 and Comparative Example 1 of the present invention;
[0038] Fig.10 1 is a charge and discharge cycle diagram of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] See also Figure 1-10 The embodiment of the present invention provides eight technical solutions: a method for in-situ construction of a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride, specifically including the following embodiments:
[0041] Embodiment 1:
[0042] Step 1, cleaning the surface of lithium metal: select a lithium metal sheet with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with tetrahydrofuran solvent, and remove impurities on the surface of the lithium metal as much as possible. After cleaning, lay the lithium sheet flat, and after the tetrahydrofuran evaporates, an artificial SEI can be constructed on the surface of the lithium metal;
[0043] Step 2, surface modification of lithium metal: pour trifluoromethanesulfonic anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step 1 horizontally into the culture dish, control the reaction time to 0.5 to 30 minutes, and after the reaction is completed, wash the surface of the lithium metal with tetrahydrofuran to remove the unreacted organic anhydride solution;
[0044] Step 3, assembling lithium metal batteries: the trifluoromethanesulfonic anhydride modified lithium metal battery obtained in step 2 is used as the negative electrode of the battery, a 25μm thick Celgard 2500 is used as a separator, and an aluminum electrode with lithium iron phosphate (LFP) as the active material is used as the positive electrode, wherein the ratio of LFP:Super P:PVDF is 8:1:1, and the electrolyte is an organic solution of ethylene carbonate (EC) and diethyl carbonate (DEC) added with 1M lithium hexafluorophosphate (LiPF6), the volume ratio of EC and DEC is 1:1, and the amount of electrolyte for each battery is controlled at 80μL. Finally, a CR-2032 battery shell is used to assemble the button battery; after all the batteries are left to stand for 4 hours, they are transferred to the LAND battery testing equipment room and subjected to cyclic charge and discharge tests in a 30°C constant temperature box.
[0045] Embodiment 2:
[0046] Step 1, cleaning the surface of lithium metal: select a lithium metal sheet with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with tetrahydrofuran solvent, and remove impurities on the surface of the lithium metal as much as possible. After cleaning, lay the lithium sheet flat, and after the tetrahydrofuran evaporates, an artificial SEI can be constructed on the surface of the lithium metal;
[0047] Step 2, surface modification of lithium metal: pour trifluoroacetic anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step 1 horizontally into the culture dish, control the reaction time to 0.5 to 30 minutes, and after the reaction is completed, wash the surface of the lithium metal with tetrahydrofuran to remove the unreacted organic anhydride solution;
[0048] Step 3, assembling lithium metal batteries: the trifluoroacetic anhydride-modified lithium metal battery obtained in step 2 is used as the negative electrode of the battery, a 25 μm thick Celgard 2500 is used as a separator, and an aluminum electrode with lithium iron phosphate (LFP) as the active material is used as the positive electrode, wherein the ratio of LFP:Super P:PVDF is 8:1:1, and the electrolyte is an organic solution of ethylene carbonate (EC) and diethyl carbonate (DEC) added with 1M lithium hexafluorophosphate (LiPF6), the volume ratio of EC and DEC is 1:1, and the amount of electrolyte for each battery is controlled at 80 μL. Finally, a CR-2032 battery shell is used to assemble the button battery; after all the batteries are left to stand for 4 hours, they are transferred to the LAND battery testing equipment room and subjected to cyclic charge and discharge tests in a 30°C constant temperature box.
[0049] Embodiment 3:
[0050] Step 1, cleaning the surface of lithium metal: select a lithium metal sheet with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with tetrahydrofuran solvent, and remove impurities on the surface of the lithium metal as much as possible. After cleaning, lay the lithium sheet flat, and after the tetrahydrofuran evaporates, an artificial SEI can be constructed on the surface of the lithium metal;
[0051] Step 2, surface modification of lithium metal: pour difluoroacetic anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step 1 horizontally into the culture dish, control the reaction time to 0.5 to 30 minutes, and after the reaction is completed, wash the surface of the lithium metal with tetrahydrofuran to remove the unreacted organic anhydride solution;
[0052] Step 3, assembling lithium metal batteries: the lithium metal battery modified with difluoroacetic anhydride obtained in step 2 is used as the negative electrode of the battery, a 25 μm thick Celgard 2500 is used as a separator, and an aluminum electrode with lithium iron phosphate (LFP) as the active material is used as the positive electrode, wherein the ratio of LFP:Super P:PVDF is 8:1:1, and the electrolyte is an organic solution mixed with ethylene carbonate (EC) and diethyl carbonate (DEC) added with 1M lithium hexafluorophosphate (LiPF6), the volume ratio of EC and DEC is 1:1, and the amount of electrolyte for each battery is controlled at 80 μL. Finally, button batteries are assembled using CR-2032 battery shells; all batteries are left to stand for 4 hours and then transferred to the LAND battery testing equipment room for cyclic charge and discharge tests in a 30°C constant temperature box.
[0053] Embodiment 4:
[0054] Step 1, cleaning the surface of lithium metal: select a lithium metal sheet with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with tetrahydrofuran solvent, and remove impurities on the surface of the lithium metal as much as possible. After cleaning, lay the lithium sheet flat, and after the tetrahydrofuran evaporates, an artificial SEI can be constructed on the surface of the lithium metal;
[0055] Step 2, surface modification of lithium metal: Pour perfluorobutyric anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step 1 horizontally into the culture dish, control the reaction time to 0.5 to 30 minutes, and after the reaction is completed, wash the surface of the lithium metal with tetrahydrofuran to remove the unreacted organic anhydride solution;
[0056] Step 3, assembling lithium metal batteries: the perfluorobutyric anhydride modified lithium metal battery obtained in step 2 is used as the negative electrode of the battery, a 25μm thick Celgard 2500 is used as a separator, and the positive electrode adopts an aluminum pole piece with lithium iron phosphate (LFP) as the active material, wherein the ratio of LFP:Super P:PVDF is 8:1:1, and the electrolyte adopts an organic solution mixed with ethylene carbonate (EC) and diethyl carbonate (DEC) added with 1M lithium hexafluorophosphate (LiPF6), the volume ratio of EC and DEC is 1:1, and the amount of electrolyte for each battery is controlled at 80μL. Finally, the button battery is assembled using a CR-2032 battery shell; all batteries are left to stand for 4 hours and then transferred to the LAND battery testing equipment room for cyclic charge and discharge tests in a 30°C constant temperature box.
[0057] Embodiment 5:
[0058] Step 1, cleaning the surface of lithium metal: select a lithium metal sheet with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with tetrahydrofuran solvent, and remove impurities on the surface of the lithium metal as much as possible. After cleaning, lay the lithium sheet flat, and after the tetrahydrofuran evaporates, an artificial SEI can be constructed on the surface of the lithium metal;
[0059] Step 2, surface modification of lithium metal: pour trifluoromethanesulfonic anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step 1 horizontally into the culture dish, control the reaction time to 0.5 to 30 minutes, and after the reaction is completed, wash the surface of the lithium metal with tetrahydrofuran to remove the unreacted organic anhydride solution;
[0060] Step 3, assembling lithium metal symmetric batteries: the trifluoromethanesulfonic anhydride modified lithium metal battery obtained in step 2 is used as the positive and negative electrodes of the battery, and a 25μm thick Celgard 2500 is used as a separator. The electrolyte is an organic solution of ethylene carbonate (EC) and diethyl carbonate (DEC) added with 1M lithium hexafluorophosphate (LiPF6). The volume ratio of EC and DEC is 1:1. The amount of electrolyte for each battery is controlled at 80μL. Finally, the button battery is assembled using a CR-2032 battery shell; all batteries are left to stand for 4 hours and then transferred to the LAND battery testing equipment room for cyclic charge and discharge tests in a 30°C constant temperature box.
[0061] Embodiment 6:
[0062] Step 1, cleaning the surface of lithium metal: select a lithium metal sheet with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with tetrahydrofuran solvent, and remove impurities on the surface of the lithium metal as much as possible. After cleaning, lay the lithium sheet flat, and after the tetrahydrofuran evaporates, an artificial SEI can be constructed on the surface of the lithium metal;
[0063] Step 2, surface modification of lithium metal: pour trifluoroacetic anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step 1 horizontally into the culture dish, control the reaction time to 0.5 to 30 minutes, and after the reaction is completed, wash the surface of the lithium metal with tetrahydrofuran to remove the unreacted organic anhydride solution;
[0064] Step 3, assembling lithium metal symmetric batteries: the trifluoroacetic anhydride-modified lithium metal battery obtained in step 2 is used as the positive and negative electrodes of the battery, and a 25 μm thick Celgard 2500 is used as a separator. The electrolyte is an organic solution of ethylene carbonate (EC) and diethyl carbonate (DEC) added with 1M lithium hexafluorophosphate (LiPF6). The volume ratio of EC and DEC is 1:1. The amount of electrolyte for each battery is controlled at 80 μL. Finally, the button battery is assembled using a CR-2032 battery shell; all batteries are left to stand for 4 hours and then transferred to the LAND battery testing equipment room for cyclic charge and discharge tests in a 30°C constant temperature box.
[0065] Embodiment 7:
[0066] Step 1, cleaning the surface of lithium metal: select a lithium metal sheet with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with tetrahydrofuran solvent, and remove impurities on the surface of the lithium metal as much as possible. After cleaning, lay the lithium sheet flat, and after the tetrahydrofuran evaporates, an artificial SEI can be constructed on the surface of the lithium metal;
[0067] Step 2, surface modification of lithium metal: pour difluoroacetic anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step 1 horizontally into the culture dish, control the reaction time to 0.5 to 30 minutes, and after the reaction is completed, wash the surface of the lithium metal with tetrahydrofuran to remove the unreacted organic anhydride solution;
[0068] Step 3, assembling lithium metal symmetric batteries: the lithium metal battery modified with difluoroacetic anhydride obtained in step 2 is used as the positive and negative electrodes of the battery, with a 25 μm thick Celgard 2500 as the separator, and the electrolyte is an organic solution of ethylene carbonate (EC) and diethyl carbonate (DEC) added with 1M lithium hexafluorophosphate (LiPF6), the volume ratio of EC and DEC is 1:1, the amount of electrolyte for each battery is controlled at 80 μL, and finally the button batteries are assembled using a CR-2032 battery shell; all batteries are left to stand for 4 hours and then transferred to the LAND battery testing equipment room for cyclic charge and discharge tests in a 30°C constant temperature box.
[0069] Embodiment 8:
[0070] Step 1, cleaning the surface of lithium metal: select a lithium metal sheet with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with tetrahydrofuran solvent, and remove impurities on the surface of the lithium metal as much as possible. After cleaning, lay the lithium sheet flat, and after the tetrahydrofuran evaporates, an artificial SEI can be constructed on the surface of the lithium metal;
[0071] Step 2, surface modification of lithium metal: pour heptafluorobutyric anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step 1 horizontally into the culture dish, control the reaction time to 0.5 to 30 minutes, and after the reaction is completed, wash the surface of the lithium metal with tetrahydrofuran to remove the unreacted organic anhydride solution;
[0072] Step 3, assembling lithium metal symmetric batteries: the heptafluorobutyric anhydride-modified lithium metal battery obtained in step 2 is used as the positive and negative electrodes of the battery, a 25 μm thick Celgard 2500 is used as a separator, and the electrolyte is an organic solution of ethylene carbonate (EC) and diethyl carbonate (DEC) added with 1M lithium hexafluorophosphate (LiPF6). The volume ratio of EC and DEC is 1:1, and the amount of electrolyte for each battery is controlled at 80 μL. Finally, the button batteries are assembled using a CR-2032 battery shell; all batteries are left to stand for 4 hours and then transferred to the LAND battery testing equipment room for cyclic charge and discharge tests in a 30°C constant temperature box.
[0073] Comparative Example 1:
[0074] The same battery assembly scheme as in Example 1 was followed, but an untreated lithium metal sheet was used as the negative electrode. The assembled CR-2032 battery was used as Control Example 1. After standing for 4 hours, a cyclic charge and discharge test was performed in a LAND test room at a constant temperature of 30°C.
[0075] Comparative Example 2:
[0076] The same battery assembly scheme as in Example 5 was followed, but untreated lithium metal sheets were used for the two electrodes of the symmetrical battery. The assembled CR-2032 battery was used as Control Example 2. After standing for 4 hours, a cyclic charge and discharge test was performed in a LAND test room at a constant temperature of 30°C.
[0077] Describe the battery performance graph as follows:
[0078] Figure 2 This is a SEM of the surface of lithium metal without any treatment. It can be clearly seen that there are many protrusions and cracks on the surface of lithium metal. These defects are the main reason for the disordered growth of lithium dendrites. In subsequent cycles, they will accelerate the consumption of lithium and electrolyte, resulting in rapid capacity decay and increased interface resistance. However, after being soaked in trifluoromethanesulfonic anhydride, such as Figure 3As shown, lithium metal reacts with trifluoromethanesulfonic anhydride to form a smooth and flat artificial SEI on its surface, which can greatly reduce the tip effect and inhibit the growth of lithium dendrites. Figure 4 , Figure 5 , Figure 6 These are the morphology images of the lithium metal surface immersed in trifluoroacetic anhydride, difluoroacetic anhydride, and perfluorobutyric anhydride. The surface is relatively broken, with more protrusions and cracks. Such a SEI surface is not conducive to uniform lithium metal deposition and will greatly increase the risk of disordered growth of lithium dendrites. Therefore, in subsequent battery testing work, only trifluoromethanesulfonic anhydride was selected as the modified solvent for lithium metal.
[0079] Figure 7 and Figure 8 These are the performance diagrams of Li-Li symmetric batteries, respectively at 0.5 mA cm -2 and 1mA cm -2 The current density of 1 mAh cm -2 .like Figure 7 As shown, at a current density of 0.5 mA cm -2 When the current density is increased to 1 mA cm -2 , Example 5 still shows a lower nucleation potential than Control Example 2, which are 20.8mV and 41.8mV respectively. The relatively low nucleation potential helps to reduce the energy barrier during lithium metal deposition, enhance the transmission capacity of lithium ions, and SEI has higher ionic conductivity, thereby improving coulombic efficiency and reducing energy loss during battery charging and discharging. Not only that, the low nucleation potential helps to achieve more uniform lithium metal deposition and reduce the formation of lithium dendrites, which is crucial to improving the cycle stability and safety of the battery.
[0080] Fig.10 The charge and discharge cycle performance diagram of Example 1 and Comparative Example 1 is shown in Figure 1. The first cycle coulombic efficiency of Example 1 is 91.13%, and the first cycle discharge specific capacity is as follows: Fig. 9 It is shown as 154.2mAh g-1, but the first cycle coulomb efficiency of control example 1 is only 80.43%, which means that the battery of control example 1 consumed more lithium source to generate SEI during the first charging process, resulting in an increase in irreversible capacity, which greatly reduced the battery performance. Since Example 1 has already constructed SEI in situ, it will not consume too much lithium source in the generation of SEI. After 300 cycles, Example 1 still has a capacity retention rate of 74.94%, while Control Example 1 has only a capacity retention rate of 60.83%. These can reflect that the in-situ SEI prepared by trifluoromethanesulfonic anhydride plays a great role in improving the performance of lithium metal batteries.
[0081] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0082] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for in-situ construction of a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride, characterized in that: The specific steps include: S1. Cleaning the surface of lithium metal: Select a lithium metal disc with a diameter of 16 mm and a thickness of 0.6 μm, clean the surface of the lithium metal with an organic solvent to remove impurities on the surface of the lithium metal, lay the lithium disc flat after cleaning, and modify the surface of the lithium metal after the organic solvent evaporates; S2, Lithium metal surface modification: pour the organic acid anhydride into a clean glass culture dish, place multiple lithium sheets cleaned in step S1 horizontally into the culture dish, control the reaction time to 0.5-30min, and after the reaction is completed, wash the lithium metal surface with an organic solvent to remove the unreacted organic acid anhydride solution; S3. Assembling lithium metal batteries or Li-Li symmetric batteries.
2. The method for in-situ construction of a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride according to claim 1, characterized in that: When lithium metal battery assembly is used in step S3, the specific steps are as follows: T1, the lithium metal disc modified with organic acid anhydride obtained in step S2 is used as the negative electrode of the battery, a 25 μm thick Celgard2500 is used as the separator, an aluminum electrode with lithium iron phosphate as the active material is used as the positive electrode, and an organic solution of ethylene carbonate EC and diethyl carbonate DEC mixed with 1M lithium hexafluorophosphate is used as the electrolyte; T2. Finally, use the CR-2032 battery shell to assemble the button battery.
3. The method for in-situ construction of a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride according to claim 2, characterized in that: In step T1, the volume ratio of EC to DEC is 1:1, and the amount of electrolyte used in each battery is controlled at 80 μL.
4. The method for in-situ construction of a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride according to claim 1, characterized in that: In step S3, when the Li-Li symmetrical battery assembly is adopted, the specific steps are as follows: E1. Select two lithium metal discs modified with the same organic anhydride in step S2 as the two electrodes of the symmetrical battery, use 25 μm thick Celgard 2500 as the separator, and use an organic solution of ethylene carbonate EC and diethyl carbonate DEC mixed with 1M lithium hexafluorophosphate LiPF6 as the electrolyte; E2. Finally, use the CR-2032 battery shell to assemble the button battery.
5. The method for in-situ construction of a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride according to claim 4, characterized in that: In step E1, the volume ratio of EC to DEC is 1:1, and the amount of electrolyte used in each battery is controlled at 80 μL.
6. The method for in-situ construction of a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride according to claim 1, characterized in that: The steps S1-S3 are all completed in a glove box, the overall atmosphere of the glove box is argon, and the oxygen content and water content are both below 0.01 ppm.
7. The method of in-situ construction of a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride according to claim 1, characterized in that: The organic solvent in step S1 is one of tetrahydrofuran, diethyl ether, methyl tert-butyl ether or ethylene glycol dimethyl ether.
8. The method for in-situ construction of a solid electrolyte interface film on a lithium metal surface using an organic acid anhydride according to claim 1, characterized in that: The organic acid anhydride in step S2 is one of trifluoromethanesulfonic anhydride, difluoroacetic anhydride, trifluoroacetic anhydride, and heptafluorobutyric anhydride, and the amount of the organic acid anhydride poured in the step S2 is sufficient to immerse the lithium metal.
Citation Information
Patent Citations
Three-dimensional porous current collector as well as preparation method and use thereof
CN104716330A
Artificial SEI material, SEI film, preparation of artificial SEI material and SEI film, and application of artificial SEI material and SEI film in metal lithium battery
CN114583172A
Laminated titanium dioxide modified diaphragm as well as preparation method and application thereof
CN114976490A
Preparation method of difluoroethylene carbonate
CN115323412A
Lithium metal fluorination high-entropy SEI layer and preparation method and application thereof
CN117638006A